Deciphering Protein Structure Identified In Cumin (Cuminum Cyminum L.) (Applied Biological Research, 2015)
Cumin (Cuminum cyminum Linn.), an important commercial seed spice  with medicinal properties, belongs to family Umbelliferae. The present  study was aimed to elucidate the high quality 3D structure and function  of cumin protein (gn50). For the prediction of secondary structure of  proteinFASTAsequenceswere used and prediction was performed using  GOR IV, SOPMA, ProFunc and PDBSum. The instability index 24.29,  isoelectric point (pI) 5.14 and Grand average hydropathicity (GRAVY)  0.751 determined from primary and secondary structural analysis  illustrated the stability of cumin protein. Stability of 3D structure of  protein was confirmed using Ramachandran plot having 80.1% residues  or empirically distributed data-points present in the structure lie in most  favoured region with the total score of 98.3%. The models were  validated using protein structure checking server SAVES.
Keywords: Cumin; isoelectric point; protein; Ramachandran plot; secondary structure